Protective effect-of melatonin against formaldehyde-induced kidney damage in rats - Zararsiz, I.; Sarsilmaz, M.; Tas, U.; Kus, I.; Meydan, S.; Ozan, E. (Sage Publications Inc, 2007)
This study was undertaken to investigate the protective effects of melatonin against formaldehyde-induced renal damage in rats. For this purpose, 21 male Wistar rats were divided into three groups. The animals in Group I were used as a control, whereas the rats in group II were injected every other day with formaldehyde. The rats in group III received melatonin daily while exposed to formaldehyde. At the end of the 14-day experimental period, all rats were killed by decapitation, and the kidneys were removed. Some of the renal tissue specimens were used for determination of superoxide dismutase, glutatione peroxidase enzyme activities, and malondialdehyde levels. The remaining kidney tissue specimens were used for light microscopic evaluation. The renal tissue activities of superoxide dismutase and glutatione peroxidase were significantly decreased, and malondialdehyde levels were significantly increased in rats treated with formaldehyde compared with those of the control animals. In the light microscopic evaluation of this group, degenerative glomerules, vacuolization and dilatation of distal tubules, and vascular congestion were detected. However, an increase was observed in activities of superoxide dismutase and glutatione peroxidase enzymes, and a decrease of malondialdehyde levels in animals treated with formaldehyde plus melatonin was observed. Furthermore, the histopathological changes caused by formaldehyde were disappeared except for minimal tubular dilatation in this group. In conclusion, the biochemical and histological findings of our study suggest that melatonin administration prevents formaldehyde-induced oxidative renal damage in rats.
10th National Anatomy Congress -- SEP 06-10, 2006 -- Bodrum, TURKEY
Keywords: formaldehyde; melatonin; kidney; rat